(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Tooth enamel is a tissue that is located on top of the dentin, covering the crown of the tooth and its neck. The enamel thickness of permanent teeth averages two to three millimeters: the enamel layer is thickest on the chewing bumps, and thinner on the side surfaces. The thickness of the enamel of baby teeth does not exceed 1 mm